Impacto da cota parte do ICMS sobre os resultados educacionais nos municípios cearenses - Barroso, Clarissa Cavalcante (2015)
This paper aims to analyses the impact of the “cota parte” of ICMS implemented by the Law 14.027/2009 in the educational results on cearenses municipalities. In fact, the change in the law was motived by the search of a better educational expends. Before, the determinant factor of the “cota parte” were the size of educational expend. However, with the new legislation the “cota parte” are link with the quality of educational results. Two models are used to investigate this relation. First, a crosssection model for 2007 and 2011. Second, a panel data model. The results shows almost any evidences about the relation between the new law and the educational results.